Texts from the Swedish Consumer Agency - Dahlberg, Simon; Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Parallel texts downloaded from the website, hallåkonsument.se, run by of the Swedish Consumer Agency.

The texts have been downloaded using the command 'w3m -dump' from an ubuntu shell, whereafter the resulting text files were stripped to contain only the interesting text (no menus and such).

Parallella texter nedladdade från webbplatsen hallåkonsument.se som drivs av Konsumentverket.

Texterna har laddats ner med hjälp av kommando 'w3m -dump' ifrån ett ubuntu-skal, varpå resulterande textfiler har skalats av till att innehålla endast den intressanta texten (inga menyer och dylikt).
Texter från Konsumentverket
Keywords: trade; handel; business activity; affärsverksamhet; Consumption and consumer behaviour; Konsumtion och konsumentbeteende; TRADE, INDUSTRY AND MARKETS; HANDEL, INDUSTRI OCH MARKNADER; Economics and Business; Ekonomi och näringsliv; Languages and Literature; Språk och litteratur; Other Legal Research; Annan rättsvetenskaplig forskning